Biomechanical phenotyping pipeline for stalk lodging resistance in maize - Kaitlin Tabaracci; Norbert T. Bokros; Yusuf Oduntan; Bharath Kunduru; Joseph DeKold; Endalkachew Mengistie; Armando McDonald; Christopher J. Stubbs; Rajandeep S. Sekhon; Seth DeBolt; Daniel J. Robertson (MethodsX, 2024)
Stalk lodging (structural failure crops prior to harvest) significantly reduces annual yields of vital grain crops. The lack of standardized, high throughput phenotyping methods capable of quantifying biomechanical plant traits prevents comprehensive understanding of the genetic architecture of stalk lodging resistance. A phenotyping pipeline developed to enable higher throughput biomechanical measurements of plant traits related to stalk lodging is presented. The methods were developed using principles from the fields of engineering mechanics and metrology and they enable retention of plant-specific data instead of averaging data across plots as is typical in most phenotyping studies. This pipeline was specifically designed to be implemented in large experimental studies and has been used to phenotype over 40,000 maize stalks. The pipeline includes both lab- and field-based phenotyping methodologies and enables the collection of metadata. Best practices learned by implementing this pipeline over the past three years are presented. The specific instruments (including model numbers and manufacturers) that work well for these methods are presented, however comparable instruments may be used in conjunction with these methods as seen fit. • Efficient methods to measure biomechanical traits and record metadata related to stalk lodging. • Can be used in studies with large sample sizes (i.e., > 1,000).